EXPLORATIVE STUDY ON THE BEHAVIOR OF POCA PARTICIPANTS IN THEORETICAL PERSPECTIVE - Muniandy, Venothiney Dewi; Chethiyar, Saralah Devi Mariamdaran (PEOPLE: International Journal of Social Sciences, 2020)
The Prevention of Crime Act (POCA) 2014 is an act enacted to deal with criminal activities such as gangs, organized crime, drugs, and human trafficking. The Act is intended to regulate criminals, gangsters, and individuals who threaten national security and related matters. Even though there are a lot of awareness programs was conducted by the government, the number of offenders under POCA still increased. The offenders of POCA has a lack of awareness about his future life and goals so that it's easy to get into the crime. The purpose of this study is to explore the behavior of the participant under the crime prevention act (POCA) based on the theory of Reality. This study used a quasi-experimental qualitative method. An interview was conducted with a randomly selected participant under this Act who received a restraining order at the Police Station, Gurun, Kedah, Malaysia. In this interview session, the researcher explored the participant's experiences, thoughts, feelings, and behaviors. The participant got benefits from this interview session. The participant gains awareness plans for the future, and be aware of the mistakes made. Participant also has thought to change negative behaviors into positive ones after this interview session. In the future, researchers can observe the offenders’ behavior after job placement. Job-related programs will help POCA participants to get awareness and achieve their goals in life.